Order Monitoring Information System with Object Modeling at PT. Multi Citra Rasa - Rahayu, Sri; Yusup, Muhamad; Kurniasih, Kurniasih; Rosdiana, Rosdiana; Kurniawan, Rano (UNIVERSITAS RAHARJA, 2024)
Information Systems are a combination of hardware components and devices. Information Systems are a collection of integrated hardware and software components and have the task of collecting, storing and processing data so as to produce digital products for the availability of information for an organization. PT. Multi Citra Rasa is a B2B company operating in the F&B sector for the food service category. One of the problems that occurs in this company is the long follow-up between departments in the customer order process, this is due to the limited information obtained. System analysis was carried out using UML (Unified Modeling Language) on the Use Case Diagram. Use Case Diagram is used to generally describe the weaknesses of the system currently running at PT Multi Citra Rasa. Data was collected through an observation process in the field, then conducting questions and answers with the users involved and looking for several references that support this research. At the system design stage, researchers also used UML in Sequence Diagrams and Class Diagrams. UML is an object-oriented system modeling, where these objects will be realized on application pages that are synchronized with user needs. Meanwhile, Class Diagrams are designed to make it easier to realize database designs into basic forms of physical data, so that in the end data processing can run optimally and the information displayed is in accordance with user requirements. This research meets the needs of company management and provides convenience to all users involved so that operational activities become more effective and efficient in the future.